2020
DOI: 10.1111/jfd.13315
|View full text |Cite
|
Sign up to set email alerts
|

Infectious salmon anaemia virus detected by RT‐qPCR in Norwegian farmed rainbow trout, Oncorhynchus mykiss (Walbaum, 1792)

Abstract: How to cite this article: Alarcón M, Moldal T, Dverdal Jansen M, et al. Infectious salmon anaemia virus detected by RT-qPCR in Norwegian farmed rainbow trout, Oncorhynchus mykiss (Walbaum, 1792).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While no evidence of causality exists, the ability to elute from erythrocytes appears to relate inversely to the susceptibility to disease. Rainbow trout can sustain ISAV infection [18,19], yet experimental infection does not appear to induce signs of ISA in this species, with the exception of a single study where ISA-like disease was observed in a few family groups [19][20][21]. Furthermore, the one reported case of natural ISAV infection in rainbow trout was not associated with disease [18].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…While no evidence of causality exists, the ability to elute from erythrocytes appears to relate inversely to the susceptibility to disease. Rainbow trout can sustain ISAV infection [18,19], yet experimental infection does not appear to induce signs of ISA in this species, with the exception of a single study where ISA-like disease was observed in a few family groups [19][20][21]. Furthermore, the one reported case of natural ISAV infection in rainbow trout was not associated with disease [18].…”
Section: Introductionmentioning
confidence: 88%
“…Rainbow trout can sustain ISAV infection [18,19], yet experimental infection does not appear to induce signs of ISA in this species, with the exception of a single study where ISA-like disease was observed in a few family groups [19][20][21]. Furthermore, the one reported case of natural ISAV infection in rainbow trout was not associated with disease [18]. In contrast, Atlantic salmon is the only species where natural outbreaks of ISA have been reported.…”
Section: Introductionmentioning
confidence: 90%